A Pragmatic Study for Enhancing Agricultural Efficiency through Labor Freedom - Kapoor, Rajni; Das, Nimai (Asian Journal of Agriculture and Rural Development, 2021)
The study aims to explore labor freedom in the agricultural sector for enhancing the efficiency of farming through policy change towards assigning property rights, rental contracts, and better wage-employment options to rural workers. Labor freedom emphasizes land reform and development policy for improving the economic status and capabilities of rural workers. The paper assessed the labor freedom index, weighted through agricultural property rights, labor wage contracts, and rural development policy. Data envelopment analysis is used to assess farm-level efficiency under the framework of Tobit regression for different size-based farm categories. Farm-level information was collected through a primary survey of 336 rural households of an advanced agricultural state in India. The study found a positive association between farm size and intensity of labor freedom, although the extent of freedom differs among farms. Size-specific variation was also observed for allocative efficiency such that marginal and medium-sized farms are more efficient than smaller ones. Tobit regression indicated labor freedom to be positively and significantly related to the efficiency of marginal, small and overall farms with enhancing efficiency of 25, 17 and nearly 20%, respectively; however, estimates of labor freedom insignificantly increased the efficiency of mediums farms, by 4.8%. This result suggests that labor freedom positive and significantly affects the efficiency of farms in general, and marginal and small farms in particular. Of course, the elasticity estimate of enhancing efficiency through labor freedom for medium farmers is found at a lower level.